Dictatorship by degrees Xi Jinping in China - Feldman, Steven P. (Steven Paul), 1954- (Lexington Books, 2021)
"Steven P. Feldman argues that Chinese political culture, based on the core principle of small group loyalties, is inherently unstable, resulting in an ongoing tendency for leaders to concentrate power in order to accomplish their goals. He examines this trend in Xi Jinping's regime through the concept of pre-totalitarianism"--